Psychomotor stimulation in babies during the first 12 months: impact of parental cell phone use - Álvarez Santos, Alexandra Paola (2025)
This study analyzed the relationship between caregiver cell phone use and the quality of psychomotor stimulation in infants during their first twelve months of life. A quantitative approach with a non-experimental, cross-sectional, and correlational design was applied. Fifty-three mother-infant dyads participated, and data were collected through direct observation, psychomotor assessments, and structured questionnaires. The findings showed that increased caregiver phone use was associated with lower quality in responsive interaction, particularly in language, fine motor skills, and social engagement. Mothers with low device use demonstrated greater eye contact, directed vocalizations, and timely affective responses during interaction with their infants. It was concluded that the constant presence of cell phones in daily contexts negatively interferes with psychomotor stimulation, emphasizing the need to promote mindful parenting practices free from digital distractions.